Complications of Postoperative Epidural Analgesia For Oncologic Surgery: A Review of 18, 895 Cases. Issue 7 (July 2019) - Su, Jackson; Soliz, Jose M.; Popat, Keyuri U.; Gebhardt, Rodolfo
Abstract : Objective: The risks of epidural analgesia (EA) differ depending on the population studied. We describe our experience with postoperative EA for oncologic surgery. Materials and Methods: We searched our Acute Pain Medicine database for cases in which postoperative EA was used between 2003 and 2012. We used word search to identify and catalog cases of neurological changes, magnetic resonance imaging or computed tomography of the spine, electromyography studies, and neurologist or neurosurgeon consultations. Medical records of patients with documented persistent neurological deficits and patients who had spine imaging or neurology consultations were reviewed further. In addition, we cross-checked medical records with billing diagnosis codes for spinal epidural abscess or hematoma. Results: We reviewed 18, 895 cases in which postoperative EA was used. Complications included neurological symptoms in 2436 cases (12.9%), epidural insertion site abnormalities in 1062 cases (5.6%), complete epidural catheter migration in 829 cases (4.4%), epidural replacement in 619 cases (3.3%), and inadvertent dura puncture in 322 cases (1.7%). There were 6 cases of persistent deficits of uncertain etiology, 4 deep spinal infections (1:4724), and 2 cases of catheter tip shearing. No spinal epidural hematomas were identified (95% confidence interval, 0-0.0002). Discussion: Our findings provide a contemporary review of some risks associated with the use of postoperative EA for patients undergoing oncologic surgery. Despite a not-uncommon incidence of neurological changes, serious complications resulting in prolonged sequelae were rare.